Beyond the Match: The Impact of Advertising on Tinder on Brand Recall among Peruvian Youth - Mena, Anthony (2024)
On the threshold of its tenth anniversary, Tinder has not only revolutionized matchmaking, but has also become an emerging platform for advertising. Despite the ease with which an ad can be dismissed with a simple gesture, this study explores whether advertising on Tinder contributes to brand recall of advertised brands among young Peruvians. It examined whether users remember brands seen on the app and how their frequencies of use affect it. The findings suggest that while sporadic users do not remember brands, those who use Tinder more frequently do, although they do not remember specific details of the advertisement. This pattern highlights the importance of user interaction with digital advertising and questions its effectiveness on Tinder, while opening avenues for future research on user experience to improve brand recall.